CARACTERIZACIÓN MOLECULAR PARCIAL DEL VIRUS DEL MOTEADO DEL CLAVEL (CarMV) PRESENTE EN LA SABANA DE BOGOTÁ - Rodríguez Sáenz, Anayervid; Departamento de Microbiología Facultad de Ciencias Pontificia Universidad Javeriana (2013)
Using an ELISA test, camation mottle virus (CarMV) was found to infect 82% of the camation samples collected from the Sabana of Bogotá. The isolated virus was mechanically inoculated on virus-free carnation plants and purified by sucrose gradient centrifugation. CarMV coat protein was analized by SDS-PAGE showing a single component of about 38 Kda. Double-stranded RNA (dsRNA) extracted from carnation infected tissue showed 3 to 5 electrophoretic components ranging between 8.0 and 0.9 Kbp. Virus particles contained a genomic RNA of about 4.0 Kbp as revealed by agarosa gel electrophoresis. It was posible to distinguished 2 groups of electrophoretic pattems using RNAse T1 digestion of the RNA contained in the CarMV purified particles.